Three days till EOC : a novella - Sukhdial, Abhimanyu, 2008- (2020)
"It is the year 2100 and water, the thing that matters to all life, is wiping out life itself. The ice sheets have melted, the Earth has passed its last cataclysmic tipping point, and now there are only 3 days until EOC: the End of Civilization. Climate scientist Graham Alison, one of the last 1,000 humans left on the planet, is racing against the odds to save the world before the last rescue shuttle leaves for the Mars colonies. Will he manage to persuade the leaders of the past to change their behavior so that the present can be different? Or will it be precious networks of family relationships across time and space that actually save humanity? This gripping work of climate fiction is 12-year-old Abhimanyu Sukhdial's first novella. It won Stone Soup Magazine's 2019 Book Contest"--
Grades 4-6